2020
DOI: 10.1111/jeb.13612
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional characterization of osteocyte volumes at multiple scales, and its relationship with bone biology and genome evolution in ray‐finned fishes

Abstract: Osteocytes, cells embedded within the bone mineral matrix, inform on key aspects of vertebrate biology. In particular, a relationship between volumes of the osteocytes and bone growth and/or genome size has been proposed for several tetrapod lineages. However, the variation in osteocyte volume across different scales is poorly characterized and mostly relies on incomplete, two‐dimensional information. In this study, we characterize the variation of osteocyte volumes in ray‐finned fishes (Actinopterygii), a cla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 123 publications
(185 reference statements)
0
33
0
Order By: Relevance
“…This is not unusual, as several studies have found that cell volume can fluctuate intra-and interspecifically (3,18,19,21). The morphology of the lacunae in Tremataspis is typical "spindle-shaped" cells that have been documented in 3D in teleosts (21), chick (57), mouse (58), and human osteocyte lacunae (59)(60)(61). In contrast, the Bothriolepis lacunae differed, from traditional spindle-shaped lacunae, to small round lacunae (fig.…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…This is not unusual, as several studies have found that cell volume can fluctuate intra-and interspecifically (3,18,19,21). The morphology of the lacunae in Tremataspis is typical "spindle-shaped" cells that have been documented in 3D in teleosts (21), chick (57), mouse (58), and human osteocyte lacunae (59)(60)(61). In contrast, the Bothriolepis lacunae differed, from traditional spindle-shaped lacunae, to small round lacunae (fig.…”
Section: Discussionmentioning
confidence: 81%
“…Osteocyte shape is an important measure, as it is relevant to their mechano-sensing function (58,63), and some studies claim that particular osteocyte shapes are more sensitive than others (64). Osteocyte shape may also be related to bone type, with lacunae in organized (e.g., lamellar or parallel-fibered) bone being more elongate and regularly shaped than in woven bone (21,65). On the other hand, the large disparity in osteocyte size is relevant to paleontological genome estimation (5,6,21,66).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations